Plan de negocio para la creación de una empresa diseñadora y elaboradora de prótesis dentales, cantón Quevedo, año 2014 - Bajaña Coello, Jorge Antonio (2015)
The present investigation called "Business Plan for the creation of a manufacturing company designer and dentures in Canton Quevedo 2014" .The based on the urgent need to best meet the needs of consumers. Looking to answer several questions, the following research question was posed How can design a business plan for the creation of a leading designer and processor of dentures in Canton Quevedo 2014? This led us to propose the following objectives; which resulted in a success. Through market research found that the project is viable, giving us a hint on the market that will penetrate and the tastes and preferences of users are met. As one of them the price that will be comfortable. The target market will be the families of Canton Quevedo. With the development of the technical study could determine the optimal location and size of the business. Based on the feasibility study shows that there is a high percentage of possible customers and a large opening for the development of this business plan, after performing the respective analysis for the implementation of the dental center, a $ is projected 16205.00, where a party with 38% equity and the other part with a loan at a financial institution 62% is financed. The reflection of financial indicators such as 2.26% of IRR and NPV $ 105,947.30 denote that the implementation of the business will be viable.